UPAYA MENINGKATKAN KETERAMPILAN MENULIS PANTUN MELALUI METODE PEMBERIAN TUGAS PADA SISWA SD - Kismono, Joko (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2019)
Lately research on improving skills has become the focus of experts, one of the skills that must be supported by the ability to write poetry. This research supports to see the improvement of poetry writing skills through the method of giving assignments to elementary students. This type of research is classroom action research. The sample of this research is 6th grade students. The technique of collecting data uses observation sheets, interviews, tests and non-tests. Data analysis uses data reduction, data presentation and conclusions, then quantitative Likert scale analysis. The results obtained from this study about increasing students in poetry writing skills using the help method in accordance with the cycle that is applied then students increase a significant increase